2024
DOI: 10.1021/acs.nanolett.4c00597
|View full text |Cite
|
Sign up to set email alerts
|

Coexisting Magnetism, Ferroelectric, and Ferrovalley Multiferroic in Stacking-Dependent Two-Dimensional Materials

Wei Xun,
Chao Wu,
Hanbo Sun
et al.

Abstract: Two-dimensional (2D) multiferroic materials have widespread application prospects in facilitating the integration and miniaturization of nanodevices. However, the magnetic, ferroelectric, and ferrovalley properties in one 2D material are rarely coupled. Here, we propose a mechanism for manipulating magnetism, ferroelectric, and valley polarization by interlayer sliding in a 2D bilayer material. Monolayer GdI 2 is a ferromagnetic semiconductor with a valley polarization of up to 155.5 meV. More interestingly, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…By contrast, the magnetic transition temperature of multilayer Cr 2 Sn 2 Te 6 is higher in thicker films . Meanwhile, the effect of layer dependence is also presented in ferrovalley material. It is found that the valley polarization can be simultaneously regulated by electric and magnetic fields in bilayer-stacked ferrovalley materials. , The above research results clearly manifest that novel physical phenomena could be expected in 2D materials by regulating their stacking thickness.…”
Section: Introductionmentioning
confidence: 78%
“…By contrast, the magnetic transition temperature of multilayer Cr 2 Sn 2 Te 6 is higher in thicker films . Meanwhile, the effect of layer dependence is also presented in ferrovalley material. It is found that the valley polarization can be simultaneously regulated by electric and magnetic fields in bilayer-stacked ferrovalley materials. , The above research results clearly manifest that novel physical phenomena could be expected in 2D materials by regulating their stacking thickness.…”
Section: Introductionmentioning
confidence: 78%
“…So far, a large variety of 2D materials beyond graphene and its derivatives have been fabricated, thanks to the advanced synthesis method, such as those of the IVA group (silicene, 3 germanene, 4 stanene, 5 and silicon carbide 6 ), the VA group or pnictogens (phosphorene, 7,8 arsenene, 9 and antimonene 10 ), hexagonal boron nitride (h-BN), 11,12 and transition-metal dichalcogenides (MX 2 , where M = Mo and W, X = S and Se), 13–16 among others. In this regard, intriguing properties, such as ferrovalley, 17,18 topological bands, 19 multiferroic, 20 and more, have been found. Investigations have explored 2D materials as potential candidates for light-emitting devices, 21,22 gas sensing, 23,24 catalysis, 25,26 photonics, 27,28 and energy production and storage, 29,30 among others.…”
Section: Introductionmentioning
confidence: 99%